KEDUDUKAN HARTA BERSAMA DAN PEWARISAN DALAM PERKAWINAN ADAT BATAK TOBA (STUDI PUTUSAN NO. 429/PDT.G/2013/PN.JKT.TIM) - ALIMUDA REZEKI HASIBUAN (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd. Yamin2. T. Keizerina Devi A3. Syafnil Gani A wife only has the right to get her own property and cannot do anything without her husband’s consent, and a son as an heir will continue his father’s offspring while a daughter only gets what her parents give her as the compensation for her good manners. When a husband dies, joint property is usually distributed according to Batak Toba adat law. In the Batak Toba adat law, there is no distribution and calculation of inheritance, but it is only based on consideration on the objects and what the heirs need. Juridical analysis on the Court’s Ruling No. 429/PDT.G/2013/PN.JKT.TIM on joint property and inheritance in the Batak Toba adat marriage law is that the judge’s decision is correct since it is in accordance with Article 5, paragraph (1) of Law No. 48/2009 on Judicial Authority.Keywords: Joint Property, Inheritance, Batak Toba Adat